Castration and Connection: Kinship Organization among Ming Eunuchs. (2nd July 2016) - Chen, Gilbert
Abstract : Until recently, our understanding of Ming eunuchs was mostly centered on their involvement in political affairs. This article draws attention to the social history of Ming eunuchs, with a particular focus on their contribution to their natal families. Despite the fact of being castrated, Ming eunuchs generally maintained close relationships with their natal kinsmen. Once they obtained political power and material wealth at court, some eunuchs employed an array of strategies to build up kinship organization among their relatives, including regulation of naming patterns, establishment of corporate land, compilation of genealogies, bestowal of protection privilege, and the practice of adoption. In the end, these eunuchs took up a powerful position — similar to that of patriarch — within the domestic area. This article therefore sheds light both on the social history of eunuchs and on the expansion of kinship organization in late imperial Chinese society.